Effects of osteopathic manipulative treatment of the pivots on lower limb function in young professional football players. (October 2022) - Thomas, Ewan; Petrucci, Marco; Barretti, Massimo; Messina, Giuseppe; Cavallaro, Antonio Rosario; Bianco, Antonino
Abstract: Introduction: The most frequent injuries in professional soccer players are those pertinent to the lower limbs. In particular, strains of the hamstrings and ligamentous injuries of the knee. Therefore, preventive measures are aimed to reduce such events. We aimed to investigate if an osteopathic manipulative treatment (OMT) of the pivots could improve lower limb function in young professional football players. Methods: Thirty-eight young male professional football players were recruited (mean age 17.8 ± 0.44 years). These were randomly assigned to an OMT or control group (n = 20 and 18, respectively). Both groups underwent osteopathic evaluation. A sit-and-reach test, a vertical jump test, a hand-grip strength test, a cervical ROM test and a balance evaluation were also performed. Results: A significant improvement (p < 0.01) was observed between pre and post measures in the OMT for dysfunctional assessment of the pivots. However, only L3 and C2 also differed from the control group post evaluation (p < 0.0001). No differences were present for any functional measure in the control group. Only the sit-&-reach of the OMT increased significantly (p < 0.001). Static balance with open eyes in the OMT, but not in the control group, improved during post evaluation (p < 0.01). Conclusion: The OMT of the pivots was able to increase the sit-and-reach measure, improve postural control with open eyes and improve dysfunctional patterns of the lumbosacral and upper cervical spine in young professional football players.